Cryptic recessive lethality of a supergene controlling social organization in ants. Issue 5 (27th December 2022) - Blacher, Pierre; De Gasperin, Ornela; Grasso, Guglielmo; Sarton‐Lohéac, Solenn; Allemann, Roxane; Chapuisat, Michel
Abstract: Supergenes are clusters of linked loci that control complex phenotypes, such as alternative forms of social organization in ants. Explaining the long‐term maintenance of supergenes is challenging, particularly when the derived haplotype lacks homozygous lethality and causes gene drive. In the Alpine silver ant, Formica selysi, a large and ancient social supergene with two haplotypes, M and P, controls colony social organization. Single‐queen colonies only contain MM females, while multiqueen colonies contain MP and PP females. The derived P haplotype, found only in multiqueen colonies, selfishly enhances its transmission through maternal effect killing, which could have led to its fixation. A population genetic model showed that a stable social polymorphism can only be maintained under a narrow set of conditions, which includes partial assortative mating by social form (which is known to occur in the wild), and low fitness of PP queens. With a combination of field and laboratory experiments, we show that the P haplotype has deleterious effects on female fitness. The survival rate of PP queens and workers was around half that of other genotypes. Moreover, P ‐carrying queens had lower fertility and fecundity compared to other queens. We discuss how cryptic lethal effects of the P haplotype help stabilize this ancient polymorphism.